IONIC WIND ON THE DESK - Коваль, Данило; Чурсанова, Марина; Дрозденко, Олександра (SWorldJournal, 2024)
An original experimental model for the ionic wind observation at home has been created in the present work. This interesting electrical phenomenon is the basis for development of ionic thrusters which make jet thrust without mechanical moving parts, with